Short Communication: Leptospirosis control based on eco-social factors: Modeling combination in Demak, Central Java, Indonesia - Rr Anggun Paramita Djati; Haryoto Kusnoputranto; Suyud Warno Utomo; Mateus Sakundarno; Pandji Wibawa Dewabrata; Habiburrachman Alfian Houzaeri Fuad; Mochammad Arief Wicaksono (Society for Indonesian Biodiversity, 2020)
Abstract. Djati RRAP, Kusnoputanto H, Utomo SW, Sakundarno M, Dewabrata PW, Duad HAH, Wicaksono MA. 2020. Short Communication: Leptospirosis control based on eco-social factors: Modeling combination in Demak, Central Java, Indonesia. Biodiversitas 21: 5818-5828. Ecological habitats and niches of leptospirosis as one of the environmental-based diseases need to be explored in an in-depth study based on eco-social analysis. The objective of this study was to develop an integrated leptospirosis control model based on eco-social factors. The location of the study was in Demak districts, Indonesia. Geographic coordinate data of cases during 2008-2018 were determined from the survey results of District Health Offices. Climatic and environmental data were obtained from Indonesian Meteorological, Climatological, Geophysical and Geospatial Information Agencies. Data on social factors were obtained by interviewing diseased persons using in-depth interview. Recorded cases and corresponding point location environmental data were then analyzed using ArcGIS and MaxEnt programs. Social network analysis was used to describe the factors involved in efforts to control leptospirosis and the relationship. The model predicted that the intervention was biological control, which had the highest leverage to reduce the morbidity rate. Health workers played an important role in efforts to control leptospirosis, although they were supported by self-supporting roles of the community. Management and control of natural and socio-environmental risk factors are very important. Combination model based on eco-social approach would be a useful tool to design and implement appropriate leptospirosis control.